Thermal storage absorber
By arranging adsorbents in a mesh pattern on heat transfer tubes with optimized wire diameter and thickness, the adsorption layer's thermal resistance and adsorbate transport resistance are minimized, enhancing the adsorbent's utilization rate and heat release output in adsorbers.
Patent Information
- Application Number
- JP2021119940
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-07-20
AI Technical Summary
Conventional adsorbers with randomly packed adsorbent layers in the adsorption layer around heat exchanger tubes face increased thermal resistance and adsorbate transport resistance as the layer thickness increases, leading to a decrease in the utilization rate of the adsorbent.
The adsorbent is arranged in a mesh shape on the outer periphery of a heat transfer tube, stacked in multiple stages with adsorbents in the same stage parallel and adjacent stages in different directions, forming a flow path for adsorbate, and the wire diameter and thickness of the adsorption layer are optimized to reduce thermal resistance and enhance adsorbate movement.
This configuration improves the adsorbent utilization rate and increases the output of cold or hot heat release over long periods, optimizing the adsorption process.
Smart Images

Figure 0007603544000001 
Figure 0007603544000002 
Figure 0007603544000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat storage adsorber. [Background technology]
[0002] Conventionally, there is known an adsorber including an adsorbent that adsorbs and desorbs evaporated adsorbates, such as water. For example, the following Patent Document 1 discloses a technique in which a working medium to be adsorbed by an adsorbent is circulated through a flow path disposed between a plurality of plate-shaped adsorbents. Also, the following Patent Document 2 discloses a technique in which a working fluid is circulated through a plurality of holes formed in a plate-shaped adsorbent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6045413 [Patent Document 2] Patent No. 5900391 Summary of the Invention [Problem to be solved by the invention]
[0004] In a conventional adsorber, an adsorption layer is formed by packing and solidifying an adsorbent around a heat transfer tube through which a heat exchange medium flows. In this adsorption layer, the adsorbent is randomly packed. In such a conventional adsorber, the thickness of the adsorption layer is increased in order to increase the amount of adsorption by adsorbing the adsorbate for a relatively long period of time, for example, one hour. However, in the case of an adsorption layer having such a packed structure, as the thickness of the adsorption layer is increased, both the thermal resistance and the transport resistance of the adsorbate increase, and the utilization rate of the adsorbent is instead reduced.
[0005] An object of the present disclosure is to realize an adsorbent structure suitable for adsorption for a relatively long period of time in a heat-storage adsorber that stores cold or hot heat by adsorbing an adsorbate into an adsorbent. [Means for solving the problem]
[0006] A first embodiment of the present disclosure relates to a heat storage adsorber that stores cold or hot heat by adsorbing an adsorbate onto an adsorbent, in which the adsorbent is stacked in a mesh-like pattern in multiple stages around a heat transfer tube through which a heat medium flows, and the adsorbents in the same stage are arranged in parallel in the same direction, while the adsorbents in adjacent stages are arranged in different directions.
[0007] That is, the adsorbent is layered in a plurality of stages in a mesh pattern, and the adsorbents in the same stage are arranged in parallel in the same direction, while the adsorbents in adjacent stages are arranged in different directions, so that flow paths are provided between the adsorbents, which serve as a path for the adsorbate to move. These flow paths reduce the resistance to the movement of the adsorbate, so that an increase in the thickness of the adsorption layer does not result in an increase in thermal resistance.
[0008] In addition to the configuration of the first embodiment, the heat-storage adsorber of the second embodiment of the present disclosure has the following features: 0.95≦w≦1.47 and 13≦H≦(1100w-161) / 52, or 1.47 <w≦3.2、かつ、13≦H≦28、 It is.
[0009] In the above relational expression, the relationship between the linear diameter w of the adsorbent and the thickness H of the adsorption layer is as follows: H=nw (where n is a natural number greater than or equal to 2) That is, an adsorption layer with a thickness of H is formed by stacking n layers of adsorbent with a wire diameter of w.
[0010] When the linear diameter w of the adsorbent and the thickness H of the adsorption layer satisfy the above-mentioned relationship, in a heat-storage adsorption device having such an adsorption layer, when the adsorbate is adsorbed for a long period of time, for example, one hour, the utilization rate of the adsorbent is improved and the output when releasing cold or hot heat is increased.
[0011] The heat-storage adsorber according to the third embodiment of the present disclosure has the same configuration as the second embodiment, and further has a wire diameter w (mm) of the adsorbent. 1.1≦w≦2.8 and The thickness H (mm) of the adsorption layer 16≦H≦21 It is.
[0012] When the linear diameter w of the adsorbent and the thickness H of the adsorption layer satisfy the above-mentioned relationship, in a heat-storage adsorption device having such an adsorption layer, when the adsorbate is adsorbed for a long period of time, for example, one hour, the utilization rate of the adsorbent is further improved and the output when releasing cold or hot heat is further increased.
[0013] A fourth embodiment of the present disclosure has the same configuration as any one of the first to third embodiments, in which the gap between adjacent adsorbents is 500 μm or less.
[0014] By making the gap between the adsorbents 500 μm or less, a path for the gaseous adsorbate to move within the adsorption layer can be secured, improving the utilization rate of the adsorbent not only on the surface but also inside the adsorption layer. The lower limit of the gap between the adsorbent tubes is not particularly limited as long as it is a value above 0 μm, but from the viewpoint of securing the movement of the adsorbate, it is desirable for it to be 50 μm or more. Effect of the Invention
[0015] Since the embodiments of the present disclosure are configured as described above, an adsorbent structure suitable for adsorption for a relatively long period of time is realized in a heat storage adsorber that stores cold or hot heat by adsorbing an adsorbate into an adsorbent. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram of an adsorption heat pump including an adsorption layer according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the structure of an adsorbent. [Diagram 3] FIG. 2 is a schematic diagram showing a detailed structure of an adsorption layer. [Figure 4]This is a graph showing the measured values of (A) average cold power output (VCP), (B) total heat storage density (Q), and (C) utilization rate (X) of the adsorbent for an adsorption layer of thickness H when seven layers of adsorbent are stacked. [Diagram 5] 1 is a graph showing the measured values of (A) average cold power output (VCP), (B) total heat storage density (Q), and (C) utilization rate (X) of the adsorbent for an adsorption layer of thickness H when 10 layers of adsorbent are stacked. [Figure 6] 1 is a graph showing the measured values of (A) average cold power output (VCP), (B) total thermal storage density (Q), and (C) utilization rate (X) of the adsorbent for an adsorption layer of thickness H when 13 layers of adsorbent are stacked. [Figure 7] 1 is a graph showing measured values of (A) average cold power (VCP), (B) total thermal storage density (Q), and (C) utilization rate (X) of the adsorbent for an adsorption bed of a comparative example. [Figure 8] FIG. 2 is a contour diagram showing the calculation results of the average cold power output (VCP) versus the wire diameter w of the adsorbent and the thickness H of the adsorption layer. [Figure 9] FIG. 2 is a contour diagram showing the calculation results of the utilization rate (X) of the adsorbent relative to the linear diameter w of the adsorbent and the thickness H of the adsorption layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] (1) Schematic configuration of the embodiment 1 is a schematic diagram of an adsorption heat pump 10 including an adsorption layer 20 according to an embodiment. The adsorption heat pump 10 includes two heat-storage adsorbers 6 and 7, two evaporators 8 and 9, connection pipes 3a, 3b, 3c, and 3d connecting the two, a plurality of valves 4a, 4b, 4c, and 4d respectively disposed in the connection pipes 3a, 3b, 3c, and 3d, and a control unit (not shown). The adsorption heat pump 10 generates cold energy from hot energy by utilizing a combination of two sets of heat-storage adsorbers 6 and 7 and the evaporators 8 and 9.
[0018] The heat-storage adsorbers 6 and 7 each include a reaction vessel 6a or 7a, an adsorbent 1 accommodated in the reaction vessel 6a or 7a, and a heat exchanger 5 that circulates a heat medium inside the reaction vessel 6a or 7a. The adsorbent 1 adsorbs adsorbate vapor, such as water vapor, generated in the evaporative condensers 8 or 9. The adsorbent 1 that has adsorbed the water vapor desorbs the water vapor using heat from a heat medium, such as hot water, flowing through the heat exchanger 5. In other words, the heat-storage adsorbers 6 and 7 adsorb the adsorbate to the adsorbent 25 (see FIG. 3) that constitutes the adsorbent 1, thereby storing cold heat or hot heat.
[0019] The evaporative condensers 8, 9 each have a pipe 8a, 9a through which the heat medium flows, and a storage container 8b, 9b for storing an adsorbate, for example, water, to be adsorbed in the adsorbent 1. In the evaporative condensers 8, 9, depending on the mode of the connected heat-storage adsorbers 6, 7, the heat medium flowing through the pipe 8a, 9a is cooled by the heat of vaporization generated when the adsorbate in the storage container 8b, 9b evaporates, or the vapor of the adsorbate in the storage container 8b, 9b is condensed and returned to a liquid.
[0020] Next, the operation of the adsorption heat pump 10 in Fig. 1 will be described. In the state shown in Fig. 1, a valve 4a arranged in the connection pipe 3a connecting the heat-storage adsorber 6 and the evaporative condenser 8 and a valve 4b arranged in the connection pipe 3b connecting the heat-storage adsorber 7 and the evaporative condenser 9 are opened by a command from the control unit, and a valve 4c arranged in the connection pipe 3c connecting the heat-storage adsorber 6 and the evaporative condenser 9 and a valve 4d arranged in the connection pipe 3d connecting the heat-storage adsorber 7 and the evaporative condenser 8 are closed.
[0021] In the heat-storage adsorber 6 and the evaporative condenser 8, which are connected via the connecting pipe 3a, the inside is depressurized by a pump (not shown) as an adsorption step. As a result, adsorbate vapor is generated in the evaporative condenser 8. The generated adsorbate vapor passes through the connecting pipe 3a (white arrow F11) into the heat-storage adsorber 6 and is adsorbed by the adsorber 1. At this time, the heat medium, for example, water, flowing through the pipe 8a of the evaporative condenser 8 is cooled by the heat of vaporization of the adsorbate. As a result, the cooled heat medium, for example, cold water, is discharged from the pipe 8a, and cold energy is supplied to the outside of the adsorption heat pump 10.
[0022] In the desorption step, a heat medium, for example, hot water, is supplied to the heat exchanger 5 of the heat-storage adsorber 7, which is connected to the heat-storage adsorber 7 and the evaporative condenser 9 via a connection pipe 3b. In the adsorber 1 of the heat-storage adsorber 7, which adsorbs the adsorbate, the adsorbate is desorbed from the adsorber 1 by the heat of the supplied heat medium. The desorbed adsorbate enters the inside of the evaporative condenser 9 as vapor (white arrow F12), and is condensed by the heat medium, for example, water, flowing through the pipe 9a, to become a liquid, for example, water. This liquid heat medium is used in the subsequent adsorption step.
[0023] In the adsorption heat pump 10 of FIG. 1, one of the heat-storage adsorbers 6, 7 adsorbs the adsorbate vapor, and the other desorbs the adsorbate, thereby continuously generating cold by supplying a relatively high-temperature liquid adsorbate, such as hot water.
[0024] As shown in Fig. 2, the adsorber 1 has a structure in which a large number of linear structures are bundled together, each having an adsorption layer 20 formed on the outer periphery of a heat transfer tube 30 into which the flow path of the heat medium in the heat exchanger 5 is subdivided within the heat storage adsorber 6, 7. In other words, the adsorbent is laminated in a mesh-like manner in multiple stages on the outer periphery of the heat transfer tube through which the heat medium flows, to form an adsorption layer. As shown in Fig. 3, the adsorption layer 20 has a mesh-like structure in which the adsorbents 25 are laminated in multiple stages, each stage being arranged in parallel with gaps 25a between them in the same direction. The adsorbents 25 in adjacent stages are arranged in different directions from each other, as shown in Fig. 3.
[0025] Let the wire diameter of the adsorbent 25 shown in Fig. 3 be w (mm), and let the thickness of the adsorption layer 20 in which a plurality of stages (4 stages as an example in Fig. 3) of the adsorbent 25 are stacked be H (mm). Then, it is desirable that 0.95 ≤ w ≤ 1.47 and 13 ≤ H ≤ (1100w - 161) / 52, or 1.47 < w ≤ 3.2 and 13 ≤ H ≤ 28. Specifically, although it will be described in detail later, it is desirable to form the adsorbent 25 with a wire diameter w and a thickness H specified in the region inside the pentagon ABCDE in the graph of Fig. 8. Note that the cross-section of the adsorbent 25 may be a substantially square shape as schematically shown in Fig. 3, or a substantially circular shape. The wire diameter w in the case of a substantially square shape represents the length of one side, and the wire diameter w in the case of a substantially circular shape represents the diameter.
[0026] Furthermore, it is more desirable that 1.1 ≤ w ≤ 2.8 and 16 ≤ H ≤ 21. Specifically, although it will be described in detail later, it is more desirable to form the adsorbent 25 with a wire diameter w and a thickness H specified in the region inside the rectangle A'B'C'D' in the graph of Fig. 8.
[0027] The gap 25a between the adsorbents 25 is desirably 10 μm or more, more desirably 20 μm or more, and most desirably 50 μm or more. Also, the gap 25a between the adsorbents 25 is desirably 1000 μm or less, more desirably 700 μm or less, and most desirably 500 μm or less.
[0028] The material of the adsorbent 25 is not particularly limited as long as it can be used as an adsorbent in a normal heat exchanger. For example, it is desirable to use silica gel, 13X zeolite, or Y-type zeolite. Also, it is desirable that a heat conduction aid such as carbon is blended in the material of the adsorbent 25.
Example
[0029] The following verification was conducted on the suitable wire diameter w of the adsorbent and the thickness H of the adsorption layer. Specifically, the inner diameter of the heat transfer tube was set to 1 cm. The heat transfer tubes provided with the adsorption layers shown below were arranged at 2 mm intervals. The material of the adsorbent 25 was mainly silica gel with a particle diameter of 74 μm, to which carbon was mixed as a thermal conduction assistant at a ratio of 10 mass % of the total. The adsorbent formed from this material in a linear shape with a wire diameter w and a substantially square cross section was layered in a mesh shape of n stages on the outer periphery of the heat transfer tube as shown in FIG. 3 to form an adsorption layer. As an example, the average cold output (VCP), total heat storage density (Q), and utilization rate (X) of the adsorbent were measured for a heat storage adsorber equipped with an adsorbent 1 having an adsorption layer formed with n=7 (FIG. 4), n=10 (FIG. 5), and n=13 (FIG. 6) when the adsorption time was 1 hour. The average cold output (kW / m 3 ) was calculated as the power per unit volume. Total heat storage density (MJ / m 3 ) was calculated as energy per unit volume. The utilization rate of the adsorbent was calculated as the ratio of the amount of adsorbate actually adsorbed to the amount of adsorbate that could theoretically be adsorbed. As a comparative example, the average cold output (VCP), total heat storage density (Q) and utilization rate (X) of the adsorbent were similarly measured for the adsorption layer 20 in which the same material as the adsorbent 25 was attached to the outer periphery of the heat transfer tube 30 in a packed structure with a predetermined thickness H (FIG. 7).
[0030] In Figures 4 to 7, (A) is a graph in which the relationship between the average cold output (VCP) and the thickness of the adsorption layer (H, unit: mm) is plotted on the vertical and horizontal axes, respectively, (B) is a graph in which the relationship between the total heat storage density (Q) and the thickness of the adsorption layer (H) is plotted on the vertical and horizontal axes, respectively, and (C) is a graph in which the relationship between the utilization rate of the adsorbent (X) and the thickness of the adsorption layer (H) is plotted on the vertical and horizontal axes, respectively.
[0031] Figure 4 shows the case where n=7, that is, the adsorption layer is formed by stacking seven layers of adsorbent. As shown in Figure 4(A), as the thickness H of the adsorption layer increases, the average cold power output (VCP) increases, reaching 40 kW / m at about 16.8 mm. 3As shown in Fig. 4(B), the total heat storage density (Q) increased as the thickness H of the adsorption layer increased, but the degree of increase seemed to approach a plateau when the thickness H of the adsorption layer reached the peak value in Fig. 4(A). As shown in Fig. 4(C), the utilization rate (X) of the adsorbent rapidly exceeded 0.75 when the thickness H of the adsorption layer exceeded 0, but it also showed a decreasing tendency at the thickness H value that peaked in Fig. 4(A). Therefore, taking Figs. 4(A) to (C) together, it was found that the combination of the thickness H of the adsorption layer of about 16.8 mm and the wire diameter w of the adsorbent divided by n of about 2.4 mm is desirable for a heat storage adsorber.
[0032] Figure 5 shows the case where n=10, that is, the adsorption layer is formed by stacking 10 layers of adsorbent. As shown in Figure 5(A), as the thickness H of the adsorption layer increases, the average cold power output (VCP) increases, reaching 40 kW / m at about 18 mm. 3 As shown in Fig. 5(B), the total heat storage density (Q) increased as the thickness H of the adsorption layer increased, but the degree of increase seemed to approach a plateau when the thickness H of the adsorption layer reached the peak value in Fig. 5(A). As shown in Fig. 5(C), the utilization rate (X) of the adsorbent rapidly exceeded 0.75 when the thickness H of the adsorption layer exceeded 0, but it also showed a decreasing tendency at the thickness H value that peaked in Fig. 5(A). Therefore, taking Figs. 5(A) to (C) together, it was found that a combination of an adsorption layer thickness H of about 18 mm and a wire diameter w of the adsorbent divided by n of about 1.8 mm is desirable for a heat storage adsorber.
[0033] Figure 6 shows the case where n = 13, that is, the adsorption layer is formed by stacking 13 layers of adsorbent. As shown in Figure 6(A), as the thickness H of the adsorption layer increases, the average cold power output (VCP) increases, reaching 40 kW / m at about 19.5 mm. 3As shown in Fig. 6(B), the total heat storage density (Q) increased as the thickness H of the adsorption layer increased, but the degree of increase seemed to approach a plateau when the thickness H of the adsorption layer reached the peak value in Fig. 6(A). As shown in Fig. 6(C), the utilization rate of the adsorbent (X) rapidly exceeded 0.75 when the thickness H of the adsorption layer exceeded 0, but it also showed a decreasing tendency at the thickness H value that peaked in Fig. 6(A). Therefore, taking Figs. 6(A) to (C) together, it was found that the combination of the thickness H of the adsorption layer of about 19.5 mm and the wire diameter w of the adsorbent divided by n of about 1.5 mm is desirable for a heat storage adsorber.
[0034] In the comparative example shown in Fig. 7, the adsorption layer does not have a laminated structure, so that the adsorption utilization rate (X) peaks at a thickness H of about 3 mm, which is less than one-fifth of that of each example, as shown in Fig. 7(C), and then drops sharply when the thickness H is increased beyond that value. The same was true for the average cold output (VCP) (Fig. 7(A)). The total heat storage density (Q) shown in Fig. 7(B) increases as the thickness H of the adsorption layer increases, as in each example.
[0035] As described above, by having an adsorption layer in which the adsorbent is stacked in multiple stages, the adsorbent comes into contact with the adsorbate more easily than in the case of a packed structure that does not have a stacked structure, and the utilization rate (X) of the adsorbent is improved, and the thickness H of the adsorption layer at which the average cold power output (VCP) is high is also increased. Note that, although there was not much difference in the total heat storage density (Q) between the examples and the comparative examples because it is thought to depend on the material of the adsorbent, the thickness H of the adsorption layer can be increased while increasing the utilization rate (X) of the adsorbent and the average cold power output (VCP), so that the total amount of heat stored in the heat storage adsorber as a whole is thought to increase.
[0036] FIG. 8 is a contour diagram created based on a three-dimensional graph in which each point plotted in FIG. 4(A), FIG. 5(A), and FIG. 6(A) is three-dimensionally plotted with the thickness H of the adsorption layer on the x-axis, the wire diameter w of the adsorbent obtained by dividing H by n on the y-axis, and the average cold power output (VCP) on the z-axis. The numerical values described in FIG. 8 represent the numerical range of the average cold power output (VCP) in the corresponding region. FIG. 9 is a contour diagram created based on a three-dimensional graph in which each point plotted in FIG. 4(C), FIG. 5(C), and FIG. 6(C) is three-dimensionally plotted with the thickness H of the adsorption layer on the x-axis, the wire diameter w of the adsorbent obtained by dividing H by n on the y-axis, and the utilization rate (X) of the adsorbent on the z-axis. The numerical values described in FIG. 9 represent the numerical range of the utilization rate (X) of the adsorbent in the corresponding region. Note that the region not shaded at the upper left of the graphs in FIG. 8 and FIG. 9 represents a region in which the numerical values could not be complemented because the value of n, which is the number of layers of the adsorbent, becomes too large.
[0037] In FIG. 8 , an adsorbent having a wire diameter w and a thickness H within a pentagon ABCDE surrounded by point A where w=1.47 and H=28, point B where w=3.2 and H=28, point C where w=3.2 and H=13, point D where w=0.95 and H=13, and point E where w=0.95 and H=17 has a wire diameter w of at least 40 kW / m 3 It can be seen that an average cooling output (VCP) of
[0038] Here, the straight line AE that passes through points A and E can be seen as a function of the wire diameter w and thickness H. If we assume that this function is H = aw + b Equation (1) Here, in the above formula (1), a represents the slope of this line, and b represents the y-intercept of this line.
[0039] The values of a and b in the above formula (1) can be found by solving the simultaneous equations obtained by substituting w=1.47 and H=28 at point A and w=0.95 and H=17 at point E into formula 1. As a result, the straight line AE is as follows: H=(1100w-161) / 52...Equation (2) Therefore, H≦(1100w-161) / 52 The region where this is the region below the line AE in FIG.
[0040] That is, the relationship between the linear diameter w of the adsorbent within the range of the pentagon ABCDE in FIG. 8 and the thickness H of the adsorption layer is as follows: 0.95≦w≦1.47 and 13≦H≦(1100w-161) / 52, or 1.47 <w≦3.2、かつ、13≦H≦28、 This is expressed as:
[0041] In other words, when the adsorbent wire diameter w and the adsorption layer thickness H satisfy the above relationship, the heat storage adsorption device using this adsorbent has a maximum capacity of 40 kW / m 3 A high average cold output (VCP) can be obtained. If this range is applied to Fig. 9, when the adsorbent wire diameter w and the adsorption layer thickness H satisfy the above relationship, the adsorbent utilization rate (X) can be approximately 0.75 or more, which is also a high value.
[0042] In FIG. 8, the adsorbent having a wire diameter w and a thickness H within the range of a rectangle A'B'C'D' surrounded by point A' where w=1.1 and H=21, point B' where w=2.8 and H=21, point C' where w=2.8 and H=16, and point D' where w=1.1 and H=16 has a wire diameter w of at least 42.5 kW / m 3 It can be seen that a higher average cold output (VCP) can be obtained by increasing the area of the rectangle A′B′C′D′. In addition, as shown in FIG. 9, the utilization rate (X) of the adsorbent within the rectangle A′B′C′D′ exceeds 0.75.
[0043] That is, the wire diameter w (mm) of the adsorbent is 1.1≦w≦2.8 and the thickness of the adsorption layer H (mm) is 16≦H≦21 As a result, a heat storage adsorber using this adsorbent can stably obtain a higher value of mean cold power output (VCP). [Explanation of symbols]
[0044] 1. Adsorbent 3a, 3b, 3c, 3d connection piping 4a, 4b, 4c, 4d valves 5 Heat exchanger 6 Adsorption device for heat storage 6a Reaction vessel 7 Adsorption device for heat storage 7a Reaction vessel 8 Evaporative condenser 8a Piping 8b Storage container 9 Evaporative condenser 9a Piping 9b Storage container 10 Adsorption heat pump 20 Adsorption layer 25 Adsorbent 25a gap 30 Heat transfer tube
Claims
1. A heat-storage adsorber that stores cold or hot heat by adsorbing an adsorbate onto an adsorbent, The adsorbent is stacked in a mesh-like pattern in multiple stages on the outer periphery of a heat transfer tube through which a heat medium flows, forming an adsorption layer, and the adsorbents in the same stage are arranged in parallel with each other in the same direction with gaps between them, while the adsorbents in adjacent stages are arranged in different directions.
2. When the wire diameter of the adsorbent is w (mm) and the thickness of the adsorption layer is H (mm), 0.95≦w≦1.47 and 13≦H≦(1100w−161) / 52, or 1.47<w≦3.2, and 13≦H≦28, 2. The heat-storage adsorber according to claim 1,
3. The wire diameter w (mm) of the adsorbent is 1.1≦w≦2.8 and The thickness H (mm) of the adsorption layer 16≦H≦21 3. The heat-storage adsorber according to claim 2, wherein
4. 4. The heat-storage adsorber according to claim 1, wherein the gap is 500 μm or less.
Citation Information
Patent Citations
Jukyozaikyushuyojutenzai
JP1976084789A
Antiscaling agent
JP1984000391A
Characteristic control device in suspension bushing of shock-absorber
JP1985045413A
Adsorbing material producing method
JP1996000992A
Method for manufacturing activated carbon compact with frame inserted
JP2006517901A
